Effect of pioglitazone on serum concentrations of osteoprotegerin in patients with type 2 diabetes mellitus - Park, Jong Suk (BioScientifica, 2011)
OBJECTIVE: Osteoprotegerin (OPG) acts as an important regulatory molecule in atherosclerosis. Recent studies report that thiazolidinediones could affect OPG expression. We investigated the relationship between OPG and inflammatory cytokines and the effects of pioglitazone (a PPARγ (PPARG) agonist) versus metformin on serum OPG levels in type 2 diabetic patients. DESIGN AND METHODS: Sixty-seven type 2 diabetic patients were included in this study. They were assigned to pioglitazone (15 mg/day, n=34) or metformin (1000 mg/day, n=33) during 24 weeks. Various anthropometric and metabolic parameters, OPG, interleukin 6 (IL6), C-reactive protein (CRP), adiponectin, and homeostasis model assessment of insulin resistance (HOMA-IR), were measured at baseline and at 6 months of treatment. RESULTS: Serum OPG levels correlated significantly with fasting plasma glucose (FPG), HbAlc, HOMA-IR, IL6, and CRP, and inversely correlated with adiponectin after adjusting for age (P<0.05). Multiple regression analysis showed that FPG, HbAlc, and adioponectin were independently correlated with OPG level. After 6 months of treatment, the reduction in FPG and HbAlc levels was similar between the two groups. Pioglitazone treatment significantly increased body mass index (P<0.05) and waist circumference (P<0.05) and decreased triglycerides (P<0.05) and HOMA-IR (P<0.01). The adiponectin concentration was increased (P<0.05), and OPG and CRP levels were decreased in the pioglitazone group (P<0.05), but were unchanged in the metformin group. The changes in serum OPG in the pioglitazone group showed significant correlation with changes in FPG, HbAlc, and adiponectin. CONCLUSIONS: In type 2 diabetic patients, pioglitazone decreases OPG levels, and this decrease in OPG levels might be associated with the increase in adiponectin.